Length of sickness absence and sustained return-to-work in mental disorders and musculoskeletal diseases: a cohort study of public sector employees - Johanna Kausto; Jaana Pentti; Tuula Oksanen; Lauri J Virta; Marianna Virtanen; Mika Kivimäki; Jussi Vahtera (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The aim of this study was to investigate the association between the length of sickness absence and sustained return to work (SRTW) and the predictors of SRTW in depression, anxiety disorders, intervertebral disc disorders, and back pain in a population-based cohort of employees in the Finnish public sector. METHODS: We linked data from employers' registers and four national population registers. Cox proportional hazards regression analysis with a cluster option was applied. SRTW was defined as the end of the sickness benefit period not followed by a recurrent sickness benefit period in 30 days. RESULTS: For depression, the median time to SRTW was 46 and 38 days among men and women, respectively. For anxiety disorders, the figures were 24 and 22 days, for intervertebral disc disorders, 42 and 41 days, and, for back pain, 21 and 22 days among men and women respectively. Higher age and the persistence of the health problem predicted longer time to SRTW throughout the diagnostic categories. Comorbid conditions predicted longer time to SRTW in depression and back pain among women. CONCLUSIONS: This large cohort study adds scientific evidence on the length of sickness absence and SRTW in four important diagnostic categories among public sector employees in Finland. Further research taking into account, eg, features of the work environment is suggested. Recommendations on the length of sickness absence at this point should be based on expert opinion and supplemented with research findings.